2022
DOI: 10.1002/jcph.2050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Renal Function on Pharmacokinetics, Pharmacodynamics, and Safety of a Single Dose of Romosozumab

Abstract: We evaluated the pharmacokinetics, pharmacodynamics, and safety of a single subcutaneous dose of romosozumab 210 mg, a monoclonal antibody against sclerostin, in an open‐label, parallel‐group study in participants with severe (stage 4) renal impairment (RI; n = 8) or end‐stage renal disease requiring hemodialysis (ESRD‐RH; n = 8), or healthy participants with normal renal function (n = 8). Compared with the group with normal renal function, the mean romosozumab exposure was 31% and 43% higher as measured by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In addition, the dose of alfacalcidol (0.25 μg/day) which had been orally administered may have been smaller than required, leading to the hypocalcemia in the romosozumab treatment in the present case. A recent pharmacokinetics/pharmacodynamics study by Hsu et al demonstrated that worsening hypocalcemia was found in patients on hemodialysis possibly due to the lack of compensatory increased PTH effect in the kidney, despite comparable levels of exposure to romosozumab between patients with normal renal function and those on hemodialysis ( Hsu et al, 2022 ). Notably, in the present case on chronic hemodialysis, oral CaSR agonist was simultaneously used with romosozumab.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the dose of alfacalcidol (0.25 μg/day) which had been orally administered may have been smaller than required, leading to the hypocalcemia in the romosozumab treatment in the present case. A recent pharmacokinetics/pharmacodynamics study by Hsu et al demonstrated that worsening hypocalcemia was found in patients on hemodialysis possibly due to the lack of compensatory increased PTH effect in the kidney, despite comparable levels of exposure to romosozumab between patients with normal renal function and those on hemodialysis ( Hsu et al, 2022 ). Notably, in the present case on chronic hemodialysis, oral CaSR agonist was simultaneously used with romosozumab.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sclerostin may contribute to phosphate homeostasis by stimulating FGF23 expression in bone [ 171 ]. Of note, romosozumab therapy can induce profound hypocalcemia in patients with CKD stages 4–5D, which may be exaggerated by concomitant treatment with calcimimetics, necessitating close monitoring of serum calcium after initiation of romosozumab treatment in this population [ 172 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…However, although bisphosphonates are the gold standard for osteoporosis treatment, they are contraindicated in severe CKD as dosing is difficult to do safely when renal clearance is inhibited ( Miller et al, 2022 ). An alternative treatment may be Romosozumab (Romo), a sclerostin inhibitor that both increases bone formation and decreases resorption ( Hsu et al, 2022 ). Clinical trials have consistently shown that monthly doses of Romo outperform bisphosphonates in increasing BMD and decreasing fracture rates in osteoporotic patients with mild to severe CKD ( Miller et al, 2022 ; Hsu et al, 2022 ; Miyauchi et al, 2022 ; Suzuki et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative treatment may be Romosozumab (Romo), a sclerostin inhibitor that both increases bone formation and decreases resorption ( Hsu et al, 2022 ). Clinical trials have consistently shown that monthly doses of Romo outperform bisphosphonates in increasing BMD and decreasing fracture rates in osteoporotic patients with mild to severe CKD ( Miller et al, 2022 ; Hsu et al, 2022 ; Miyauchi et al, 2022 ; Suzuki et al, 2022 ). While Romo is currently FDA-approved for use in high-risk postmenopausal osteoporosis ( Hsu et al, 2022 ), further investigation is needed to determine its efficacy in increasing bone mass in DKD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation